Adenoid cystic carcinoma of the mobile tongue: A rare case - Pavitra Baskaran; R Mithra; M Sathyakumar; Satyaranjan Misra (Wolters Kluwer Medknow Publications, 2012)
Adenoid cystic carcinoma (ACC) occurs more commonly in the minor salivary glands of the palate on than the tongue. ACC is a malignant neoplasm that accounts for 1-2% of all head and neck malignancies and 10-15% of all salivary gland malignancies. ACC affects the exocrine glands at any site, but the parotid gland is the most common site in the head and neck region. Many factors should be taken into account in the prognosis of ACC, including the histological and clinical stages of the disease. The most striking feature of ACC is that it is locally aggressive, with a high recurrence level, perineural invasion and distant metastases, especially to the lungs and bones. The most common presentation histologically is the presence of cribriform appearance (Swiss cheese pattern). The present case is a rare one present on the tongue.